Revitalizing performance: Exploring the influence of sports massage and PNF stretching on lactic acid recovery in females futsal athletes - Zubaida, Ida; Dhani, Danang Prama; Anugrah, Sendy Mohamad; Triprayogo, Rian (Journal Sport Area, 2023)
Elevated levels of lactic acid in the blood and muscles following intense training or competition can have detrimental effects on physical performance and increase the likelihood of injury. Therefore, it is crucial to identify effective recovery techniques to mitigate fatigue promptly. The objective of this study was to assess the impact of sports massage and the Proprioceptive Neuromuscular Facilitation (PNF) method on the recovery of lactic acid in athletes. This study employed a true-experimental design using a pretest-posttest without a control group. A sample of 20 female futsal athletes was divided into two groups: the sports massage group (SM) consisting of 10 participants, and the PNF method group also comprising 10 participants. Lactic acid levels were assessed before exercise, immediately after completing the anaerobic exercise, and immediately after the recovery intervention based on the respective group allocation. The results showed an increase in lactic acid after anaerobic exercise in both groups. The SM group experienced a significant decrease compared to the PNF group which did not experience a significant decrease. A significant disparity was observed in the mean lactic acid levels between the two groups in the post-test data. In conclusion, the application of sports massage following anaerobic exercise proves to be effective in reducing lactic acid concentrations in futsal athletes compared to the PNF method. The findings of this study are anticipated to yield advantages for coaches, sports medical teams, and athletes by lowering lactic acid levels, enhancing sports performance, and mitigating injury risks. Practically, the findings underscore the potential benefits of incorporating a 15-minute sports massage into the recovery routine of female futsal players.